Gender Involvement and Productivity in ICT Sector on Economic Development in Some EU Countries - Nicoleta Daniela IGNAT; Anamaria VARTOLOMEI (Communications of International Proceedings, 2020)
The Information and Communication Technology (ICT) sector has a significant impact in most European Union (EU) member states on their economic development. The aim of this paper is to analyze the impact of the ICT sector in the economic development of some EU member states and the degree of involvement of women in the development of this sector. In the first part of the paper, the productivity of employees in the ICT sector was determined and analyzed. In the second part of the paper, an analysis was made that aimed to determine the degree of women's involvement in the development of the ICT sector. This analysis focused on both the economic and the social side in terms of the accessibility of the ICT sector among women. The investigation shows that the share of women employed in the ICT sector is relatively low in all EU Member States included in the analysis. The results of this paper provide a tool that can be used by decision makers in the ICT sector by capitalizing on the creative potential of women who can work in this sector. As a perspective, the observance of the provisions of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) by ensuring equal opportunities in the ICT sector among women should be considered.
Keywords: labor productivity; ICT sector; women's employability.